Designing data-intensive applications : the big ideas behind reliable, scalable, and maintainable systems - Kleppmann, Martin (O'Reilly, 2017)
"Data is at the center of many challenges in system design today. Difficult issues need to be figured out, such as scalability, consistency, reliability, efficiency, and mainteinability. In addition, we have an overwhelming variet of tools, including relational databases, NoSQL datastores, stream or batch processors, and message brokers. What are the right choices for your application? How do you make sense of all these buzzwords? In this practical and comprehensive gjuide, author Martin Kleppmann helps you navigate this diverse landscape by examining the pros and cons of various technologies for processing and storing data. Software keeps changing, but the fundamental principles remain the same. With this book, software engineers and architects will learn how to apply those ideas in practice, and how to make full use of data in modern applications."--Resumé vydavatele
Obsahuje rejstřík
Keywords: data; zpracování dat; skladování dat; databázové systémy; data processing; data warehousing; database management systems; příručky; handbooks and manuals